Social Media Reconstructs Dalihan Na Tolu Among Batak - Eva Solina Gultom; Komang Wahyu Rustiani (Institute of Advanced Knowledge and Science, 2026)
The rapid development of digital technology has transformed cultural communication and identity construction among younger generations in Indonesia. Batak Toba youth increasingly engage with social media platforms such as TikTok, Instagram, and YouTube to access, share, and reinterpret the cultural values of Dalihan Na Tolu in contemporary digital spaces. Previous studies mainly discuss Dalihan Na Tolu from philosophical and traditional cultural perspectives, while limited research examines its digital representation among Batak Toba youth. This study analyzes how Batak Toba youth represent and preserve Dalihan Na Tolu through digital media in the digital era. The findings show that digital media has a dual impact on cultural preservation. Globalization and modern lifestyles reduce youth participation in traditional ceremonies and weaken the use of Batak language; however, social media also functions as a platform for cultural learning, identity reconstruction, and cultural dissemination. Batak Toba youth actively preserve cultural values by sharing digital content related to Batak traditions, music, language, and customary practices. This study highlights the relationship between youth digital participation and the reconstruction of Dalihan Na Tolu within contemporary digital culture. Digital platforms can function as strategic media for sustaining local cultural identity among younger generations through adaptive and participatory cultural practices.